THE ROLE OF DAKWAH IN COMMUNITY EMPOWERMENT IN THE INDUSTRIAL ERA 4.0 - Muzayyanah Yuliasih (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
Background,Da'wah is not only lectures from the pulpit, but da'wah can also be realized through concrete actions to achieve a prosperous human life. The function of da'wah in community empowerment is about how to socialize the values ​​of Islamic teachings in building the process of community change, because da'wah itself means changes to a better social self order. The author wants to describe the function of da'wah in human empowerment, which is actually part of the role of the da'i to participate in progress. Method, The research method used in this research is a qualitative method. The selection of this method is intended to find out how the data from the findings can be found, collected, processed, and analyzed. Discussion, To achieve the goals of da'wah, especially in the context of empowerment, focus, Da'wah methods and materials must be directed at the characteristics of development, namely: from: da'wah actors to the community, it will be institutionalized. Second, missionaries and the community must be closer to a common vision, because the preacher is not only responsible for transmitting but also as a bridge to facilitate the community. Third, the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it. namely: from: da'wah actors to the community will be institutionalized. Second, missionaries and the community must be closer to a common vision, because the preacher is not only responsible for transmitting but also as a bridge to facilitate the community. Third, the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it. namely: from: da'wah actors to the community will be institutionalized. Second, missionaries and the community must be closer to a common vision, because the preacher is not only responsible for transmitting but also as a bridge to facilitate the community. Third, the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it. missionaries and the community must be closer to a common vision, because the preacher is not only responsible for transmitting but also as a bridge to facilitate the community. Third, the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it. missionaries and the community must be closer to a common vision, because the preacher is not only responsible for transmitting but also as a bridge to facilitate the community. Third, the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it. the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it. the content of da'wah is no longer to describe community problems that need to be resolved by other parties, but rather to facilitate the community to understand itself, its problems and potential. , for social or political transitions. and the psychological aspects of what society wants. Fourth, da'wah must be able to create an atmosphere where the community has the capacity and potential to generate knowledge and analyze it.